Tedung Bali Craft Business Development: SWOT Analysis and Marketing Strategy - Nyoman Dwika Ayu Amrita; Made Mulia Handayani (Universitas Pendidikan Ganesha, 2021)
The local potential of the cultural heritage must be able to improve the village economy and the welfare of micro business craftsmen. Tedung is one of the medium of Hinduism ceremony. There is quite a tight competition in Tedung marketing. Marketing is difficult because people don't buy Tedung every day. The types of Tedung handicraft products produced by craftsmen in Mengwi village are still limited with several designs, even though according to their needs and functions. Strategic planning for business development needs to be made so that the operations of Tedung craftsmen can run effectively and efficiently. This study aims to formulate a business development strategy and make Tedung, the handicraft business of the Tedung as an economic booster for the community. This study uses descriptive qualitative research methods with SWOT analysis. This method is able to analyze strengths, weaknesses, opportunities and threats. The data were obtained from interviews with business owners and consumers. The research stages consisted of literature studies, field studies, problem formulation, conducting data analysis using SWOT, formulating marketing strategies for business development for Tedung craftsmen. The target output is that the craftsmen have the knowledge to develop business with increasing efficiency, productivity, scale of production and business competitiveness to get a better welfare.